Autistic adults’ experiences of financial wellbeing: Part II - Pellicano, Elizabeth; Hall, Gabrielle; Ying Cai, Ru (Autism : the international journal of research and practice, 2024)
Financial wellbeing is an important component of people’s overall wellbeing, reflecting the capacity to live a comfortable and fulfilling life. Yet virtually nothing is known about this topic for autistic people. This study addressed this gap using a two-phase sequential mixed-methods design. Here, we report on findings from the Phase 2 qualitative study. In this study, 21 autistic participants were purposively selected based on the status of their financial wellbeing, including 12 people with high, and 9 with low, financial wellbeing, and interviewed by an autistic researcher. We identified four themes through reflective thematic analysis. Having access to a stable income made an enormous difference to people’s financial wellbeing. Participants emphasised how their broader social supports, especially family support, shaped their financial wellbeing. Yet, planning financially was often challenging, especially for people who had insufficient money to meet their basic needs. Nevertheless, our participants reported a strong drive to stay in control and avoid unnecessary risk. Our findings revealed how much money matters in autistic people’s lives. Future research should investigate the ways in which autistic people could secure more reliable incomes and identify the most effective ways to support them to achieve financial resilience. Lay abstract Money matters in people’s lives. It helps to meet people’s basic needs (food, clothes, shelter) and live the lives they want to. When people talk about ‘financial wellbeing’, they mean how much you feel in control over day-to-day finances and how much freedom you have to make choices to enjoy life. We don’t know what autistic people think about these things. That’s why we did our study. We spoke to 21 autistic adults (24–69 years) about how they felt about their financial situation. We deliberately spoke to people who had told us previously they felt ‘financially well’ or ‘financially unwell’ so we could hear a range of opinions. Autistic people told us financial wellbeing meant having enough money to pay for their basics needs, to have a safety net for unexpected bills and not having to worry about money now or in the future. But many felt that good financial wellbeing was not possible for them. They often did not have a stable income to cover day-to-day expenses. This limited the choices they could make. Despite these challenges, autistic people told us they worked hard to budget and save money when they could – because feeling financial insecure was just too stressful, especially when they could not rely on family or friends for support. It made them feel mentally unwell. Our study shows there are many factors that influence autistic people’s financial wellbeing. We need more research to help us understand how autistic people can be supported to achieve financial security.